Curriculum Innovation for Future Workforce Preparation in Higher Education: A Systematic Literature Review Using Text Mining - Rudi Susilana; Gema Rullyana (APS-TPI, 2025)
Background of study: The rapid growth of Industry 4.0 and global labor market shifts push higher education to redesign curricula toward innovation, digitalization, and sustainability. Equipping graduates with 21st-century skills, employability, and adaptability is essential to prepare them for an increasingly complex workforce.Aims and scope of paper: This study aims to identify global trends in curriculum innovation for future workforce preparation in higher education (2020–2024). It examines dominant research clusters, the alignment of curriculum reforms with SDGs, and highlights areas that remain underexplored.Methods: A systematic literature review (SLR) combined with text mining was conducted using Scopus as the primary database. A total of 247 peer-reviewed documents were analyzed through bibliometric mapping, keyword co-occurrence, topic modeling using Latent Dirichlet Allocation (LDA), and semantic mapping via multidimensional scaling (MDS).Result: The findings show substantial publication growth, dominated by four key clusters: curriculum design and pedagogy, technology integration, sustainable curriculum, and blended/online learning. Emerging but less explored topics include curriculum decolonisation, problem-based learning, methodological literacy, and digital assessment. International collaboration is moderate (17.81%), though Southeast Asia and Africa show growing potential. Highly cited studies focus on digital transformation during COVID-19, online assessment integrity, and AI integration into curriculum frameworks.Conclusion: This study shows that curriculum innovation is mainly driven by digitalization and sustainability, while areas like decolonisation and methodological innovation are still lacking. The results provide theoretical, practical, and policy implications for designing adaptive, future-oriented curricula and open avenues for global collaboration and longitudinal studies in the field.